56.6k views
11 votes
0.46 + (-0.642)

Please help!! Thank you!!

User TBhavnani
by
4.8k points

1 Answer

5 votes

Answer:

-0.182

Explanation:

Given expression:

  • 0.46 + (-0.642)

It should be noted that;

1. Positive integer + (Negative integer) = Positive integer - Positive integer

  • a + (-b) = a - b

2. Positive integer - (Negative integer) = Positive integer + Positive integer

  • a - (-b) = a + b

Our case is point 1. Therefore,

  • ⇒ 0.46 + (-0.642)
  • ⇒ 0.46 - 0.642
  • -0.182
User Muhammad Raza
by
4.0k points